Morphological patterns of extrafloral nectaries in woody plant species of the Brazilian cerrado - Machado, S. R. [UNESP]; Morellato, L. P. C. [UNESP]; Sajo, M. G. [UNESP]; Oliveira, P. S. (Wiley-Blackwell, 2008)
Extrafloral nectaries are nectar-secreting structures that are especially common among the woody flora of the Brazilian cerrado, a savanna-like vegetation. In this study, we provide morphological and anatomical descriptions of extrafloral nectaries (EFNs) occurring on vegetative and reproductive organs of several plant species from the cerrado, and discuss their function and ecological relevance. We describe the morphology and anatomy of EFNs of 40 species belonging to 15 woody families using scanning electron microscopy and light microscopy. We categorise EFNs following a structural-topographical classification, and characterise the vascularised and complex nectaries, amorphous nectaries and secretory trichomes. Fabaceae, Bignoniaceae, Malpighiaceae and Vochysiaceae were the plant families with the majority of species having EFNs. Ten species possess more than one morphotype of gland structure. Observations and experimental field studies in the cerrado support the anti-herbivore role of EFN-gathering ants in this habitat. Additional morphological studies of EFNs-bearing plants, including other growth forms (e.g. herbs and lianas), are being undertaken and will hopefully cast further light on the ecological relevance of these glands in the cerrado, especially with respect to their attractiveness to multiple visitors.
Keywords: ant-plant mutualism; cerrado; extrafloral nectary; nectary anatomy; savanna